2022
DOI: 10.1002/adfm.202207094
|View full text |Cite
|
Sign up to set email alerts
|

Crystallinity Regulated Functional Separator Based on Bimetallic NixFey Alloy Nanoparticles for Facilitated Redox Kinetics of Lithium–Sulfur Batteries

Abstract: The practical application of lithium–sulfur batteries (LSBs) is limited by the shuttle effect of lithium polysulfides (LiPSs), large volume expansion, and sluggish conversion kinetics of sulfur. Herein, the crystallinity regulation of NixFey alloy anchored on oxidized carbon nanotube/nitrogen‐doped graphene (NixFey@OCNT/NG) for application of a functional separator into LSBs is demonstrated. A low crystalline NixFey@OCNT/NG (LC‐NixFey@OCNT/NG) modified polypropylene separator is systematically compared with it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…The high areal capacity of 2.7 and 3.8 mAh cm –2 can still be obtained after 100 cycles at a current density of 0.5 mA cm –2 (Figure b). Additionally, recently published studies (Figure c) on modified separators were compared in terms of different aspects. , These results further proved that the 3DCS-FMO@C separator can still effectively improve sulfur electrochemistry and inhibit the shuttling of LIPSs in the case of high sulfur loading and poor electrolyte.…”
Section: Results and Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The high areal capacity of 2.7 and 3.8 mAh cm –2 can still be obtained after 100 cycles at a current density of 0.5 mA cm –2 (Figure b). Additionally, recently published studies (Figure c) on modified separators were compared in terms of different aspects. , These results further proved that the 3DCS-FMO@C separator can still effectively improve sulfur electrochemistry and inhibit the shuttling of LIPSs in the case of high sulfur loading and poor electrolyte.…”
Section: Results and Discussionmentioning
confidence: 56%
“…Compared with the highly crystalline HC-Ni x Fe y @OCNT/NG, the low-crystalline and amorphous nanostructure has an unsaturated electronic structure, numerous original random bonds, and abundant defect sites, which can provide effective lithiophilic sites. These features enable the lithium deposition of lithium anode in the process of plating and stripping . However, the active site of these materials is a single site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[118] It was also reported that separator engineering may catalyze the SRR process and inhibit the shuttle effect of lithium polysulfides in Li─S cells. [119] In view of these outstanding works, separator engineering may be useful in Zn─I 2 batteries to some extent, as it also faces serious problems of Znion batteries and the formidable shuttle effect, and sluggish IRR kinetics.…”
Section: Separator Engineeringmentioning
confidence: 99%
“…23 Notably, the galvanostatic discharge/charge profiles of Zn−I 2 batteries using NiSAs-HPC/I 2 cathode possessed a lower potential polarization (38 mV) compared with that of the Zn−I 2 batteries using a HPC/I 2 cathode (61 mV). 45,46 The self-discharge behaviors of Zn−I 2 batteries using NiSAs-HPC/I 2 and HPC/I 2 cathodes were also investigated. As displayed in Figure 3f, the open-circuit voltage for the NiSAs-HPC/I 2 cathode delivered ultrahigh stability for ∼100 h with higher voltages, thereby suggesting that polyiodide dissolution and shuttling can be well suppressed.…”
mentioning
confidence: 99%